2021
DOI: 10.1186/s12866-021-02161-x
|View full text |Cite
|
Sign up to set email alerts
|

EHEC O111:H8 strain and norovirus GII.4 Sydney [P16] causing an outbreak in a daycare center, Brazil, 2019

Abstract: Background This study describes the investigation of an outbreak of diarrhea, hemorrhagic colitis (HC), and hemolytic uremic syndrome (HUS) at a daycare center in southeastern Brazil, involving fourteen children, six staff members, six family members, and one nurse. All bacterial and viral pathogens detected were genetically characterized. Results Two isolates of a strain of enterohemorrhagic Escherichia coli (EHEC) serotype O111:H8 were recovered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The strains with eae + and bfp + were marked as typical EPEC (tEPEC), and the strains with eae + , bfp – , stx1 – , and stx2 – were recorded as atypical EPEC (aEPEC) ( Spano et al, 2021 ). Among the EPEC ( n = 105) downloaded in this study, atypical EPEC covered a relatively high proportion (75.24%), which was similar to the results of other studies ( Afset et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strains with eae + and bfp + were marked as typical EPEC (tEPEC), and the strains with eae + , bfp – , stx1 – , and stx2 – were recorded as atypical EPEC (aEPEC) ( Spano et al, 2021 ). Among the EPEC ( n = 105) downloaded in this study, atypical EPEC covered a relatively high proportion (75.24%), which was similar to the results of other studies ( Afset et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Strains can be identified according to the characteristic virulence genes of different DEC categories: stx1 , stx2 , and eae in STEC; aggR and astA in EAEC; invE and ipaH in EIEC; est and elt in ETEC. Furthermore, typical ( eae + , bfp + ) EPEC and atypical ( eae + , bfp – , stx1 – , stx2 – ) EPEC can be distinguished ( Fujioka et al, 2013 ; Rodrigues et al, 2016 ; Spano et al, 2021 ). Some studies have shown the association between EPEC and diarrhea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, GII.2[P16] has been demonstrated not only as the cause of acute gastroenteritis but also detected in oysters that could be a potential source for foodborne transmission to humans ( 28 ). The outbreaks were also attributable to the emergence of GII.4[P16] and GII.4[P31] ( 29 , 30 ). This study aimed to investigate the prevalence of norovirus and to identify the dynamics of norovirus recombinant strains circulating in children hospitalized with acute gastroenteritis in Chiang Mai, Thailand from 2017 to 2018.…”
Section: Introductionmentioning
confidence: 99%